THERAPEUTIC AND TACTICAL ASPECTS IN THE DEVELOPMENT OF PSYCHOEMOTIONAL DISORDERS IN PERINATAL WOMEN AGAINST THE BACKGROUND OF COVID-19 INFECTION (Conferencea, 2022)
To develop therapeutic and tactical aspects in the development of psychoemotional disorders in pregnant women and young mothers against the background of COVID-19 infection.